An Odontoma Found in the Wake of Maxillary Sinusitis Onset. (7th December 2013) - Sotobori, Megumi; Marukawa, Kohei; Higuchi, Masatoshi; Nakazawa, Ryuichi; Moroi, Akinori; Ishihara, Yuri; Iguchi, Ran; Kosaka, Akihiko; Ikawa, Hiroumi; Ueki, Koichiro
Abstract : Sinusitis of dental origin is a relatively frequent entity, and odontomas are considered to be the most common odontogenic tumors of the oral cavity. Eruption and infection of odontomas are extremely rare. Here, we report an interesting case where odontoma was found in the wake of the maxillary sinusitis onset.